Women in dentistry: A perspective on major universities in Saudi Arabia. Part 2: Analysis and statistical data - Randa E. Shaker; Amani A. Babgi (Saudi Dental Journal)
Purpose and significance: The purposes of this study were to: (1) report the number of female graduates from the two oldest dental schools in Saudi Arabia; (2) compare the number of male and female graduates per year from these two major schools; and (3) compare these numbers of female dental graduates to those in the United States for the most recent year available, 2007. Methods: This study was conducted using a descriptive non-experimental design. The study sample was the number of dental school graduates from the two major dental schools in Saudi Arabia. Results: There were 1621 graduates of the College of Dentistry of King Saud University (KSU) since its inception up to 2007 of which 853 graduates were males and 768 were females, respectively. The total number of graduates from the Faculty of Dentistry of King Abdulaziz University (KAU) since its inception up till 2007 was 628 of which 264 were males and 364 were females. There was no statistically significant difference between the total number of male and female dental school graduates, although there was a significant difference between KSU and KAU dental schools. The proportion of female graduates from the two major Saudi dental schools was just over 50 % in 2007, which is slightly higher than the 45% female graduates from dental schools in the United States and Puerto Rico. Conclusions: Females currently comprise approximately half of the enrolled dental students at the KSU and KAU, a percentage slightly greater than that in the United States. The substantial enrollments suggested that women in Saudi Arabia consider dentistry to be an excellent career choice. Keywords: Saudi Arabia, Universities, Dentistry, Women, History